New species of Elachistinae (Lepidoptera: Elachistidae) from Cameroon and the Democratic Republic of the Congo - Sruoga, Virginijus; de Prins, Jurate (Zootaxa, 2011)
No Elachistinae have ever been recorded from Cameroon and only one species (Eretmograptis coniodoxa) was described by Meyrick in 1938 from the Democratic Republic of the Congo. Here, we present ten new species of the subfamily Elachistinae from Central Africa: Elachista cordata sp. n., Urodeta absidata sp. n., U. aculeata sp. n., U. crenata sp. n., U. cuspidis sp. n. U. faro sp. n., U. tortuosa sp. n. from Cameroon and U. acerba sp. n., U. bucera sp. n., U. talea sp. n. from the Democratic Republic of the Congo. The new species are diagnosed and illustrated with photographs of the adults and genitalia.